The Archives of the Institute of Oriental Studies of Sarajevo - Spaho, Fehim Dž. (Prilozi za orijentalnu filologiju, 2017)
This article contains a survey of the material kept at the Archives of the Institute of Oriental Studies of Sarajevo. The survey consists of two parts - the original material and material on microfllms and photocopies. In the chapter Original material a survey of holdings and collections of the original material kept at the Archives has been given. The collection Manuscripta turcica contains material from the 16th through 19th centuries. In three inventory books 7.156 numbers have been entered. The collection contains fermans, berats, bujruldijas, court decisions, extracts from summary defters, fmancial documents, etc. A supplement to this collection contains summaries of several more interesting documents. The collection of sidžils. This collection contains 66 sidžils (bookkeeping registers of local courts) from the middle of the 19th century to the end of the. Ottoman rule in Bosnia and Herzegovina. The importance of these sources for the study of history of various regions has been emphasized. At the end a summary survey of the number of sidžils of definite kadiluks and the years they comprise has been provided. The holdings of Vilajetski arhiv. These are the biggest holdings of the Archives of the Institute and they number about 200.000 documents. They contain materials which appeared in the last thirty years or so of the Turkish administration in Bosnia and Herzegovina. Regesta for about 6.000 subjects have been made. In addition to individual documents, 450 books have been preserved, as well as protocols which registered shipped and received material, with dates of shipment and receipt and a brief summary of documents. The supplement to these holdings brings a number of summaries of more interesting documents. The collection of tapijas. Tapijas are documents concerning proprietorship of land. All the tapijas in the collection date from the second half of the 19th century. This material is classified according to kadiluks and inside this classification, according to years. In the chapter on Microfilms and Photocopied Material, a survey of photographed material in this country and abroad has been provided. In this country the microfilming of a certain number of Turkish documents from Dubrovnik, Skoplje, Zagreb and Sarajevo has been carried out; the same thing has been done abroad - in Paris, Vienna, Warsaw, Ankara and Istanbul. Doubtless the most valuable and numerous material comes from Istanbul, the seat of the Ottoman Empire for many years. Defters concerning all Yugoslav lands have been primarily filmed. The article provides a survey of defters dealing with individual sanjaks, whose photocopies are kept at the Institute Archives. A part of the material concerning the First Serbian Uprising has been filmed as well. At the end of the survey a brief review of editions of Turkish sources and some studies resulting from work on these sources prepared by the workers of the Oriental Institute has been given.